Fetal transcerebellar diameter and transcerebellar diameter – abdominal circumference ratio as a menstrual age independent parameter for gestational age estimation with grading of cerebellar - Sharma, Gaurav; Ghode, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: It is important for achieving an uneventful gestation to have a sensitive, specific and age independent obstetric biometric parameter which stays constant throughout the gestation. Transcerebellar diameters (TCD), TCD/ abdominal circumference (AC) ratio are reliable, constant predictors to assess the gestational age and to evaluate fetal growth. Along with TCD, the morphology of the cerebellum also changes gradually with the advancing gestation. The aim of the study was to evaluate TCD and TCD/AC ratio in singleton uncomplicated pregnancy in assessing fetal gestational age and growth and to evaluate the morphological changes in the appearance of the cerebellum with advancing gestation and categorizing it into three grades system. Methods: Prospective cross sectional study carried out in 100 singletons uncomplicated pregnancy between 12-40 weeks of gestation attending antenatal ultrasound clinics of DMIMS Sawangi, Wardha. Morphology of cerebellum was studied and categorized on USG with measurement of TCD, AC, and TCD/AC ratio. Results: There was a significant linear correlation of TCD; AC with GA.TCD/AC ratio for normal fetal growth with gestational age from 12-40weeks was found to be constant with a mean of 13.75.Cerebellar grading was 27% in grade I, 40% in grade II and 33% in grade III. The median GA and TCD was 18 weeks and 17mm for grade I, 27 weeks and 27mm for grade II and 34 weeks and 42mm for grade III. Conclusions: Significant linear relation of TCD with GA indicating the reliability of this biometry in estimating gestational age and assessing fetal growth. TCD/AC ratio remains fairly constant throughout the gestation and is a sensitive gestational age independent parameter and a good predictor for fetal growth monitoring. Ultrasonography of posterior fossa demonstrated gradual morphological changes in the cerebellum.